SENP3 facilitates M1 macrophage polarization via the HIF-1α/PKM2 axis in lipopolysaccharide-induced acute lung injury. Issue 1 (January 2023) - He, Shuangjun; Fan, Chenyu; Ji, Yiming; Su, Qian; Zhao, Feng; Xie, Cuiying; Chen, Xuelian; Zhang, Yang; Chen, Yi
M1/M2 macrophage polarization plays a pivotal role in the development of acute lung injury (ALI). The hypoxia-inducible factor-1α/pyruvate kinase M2 (HIF-1α/PKM2) axis, which functions upstream of macrophage polarization, has been implicated in this process. The function of HIF-1α is known to be tightly regulated by SUMOylation. Upregulation of SUMO-specific peptidase 3 (SENP3), a deSUMOylation enzyme, is induced by reactive oxygen species (ROS), which are abundantly produced during ALI. To explore the links between SENP3, macrophage polarization, and lung injury, we used mice with Senp3 conditional knockout in myeloid cells. In the lipopolysaccharide (LPS)-induced ALI model, we found that in vitro and in vivo SENP3 deficiency markedly inhibited M1 polarization and production of pro-inflammatory cytokines and alleviated lung injury. Further, we demonstrated that SENP3 deficiency suppressed the LPS-induced inflammatory response through PKM2 in a HIF-1α-dependent manner. Moreover, mice injected with LPS after PKM2 inhibitor (shikonin) treatment displayed inhibition of M1 macrophage polarization and reduced lung injury. In summary, this work revealed that SENP3 promotes M1 macrophage polarization and production of proinflammatory cytokines via the HIF-1α/PKM2 axis, contributing to lung injury; thus, SENP3 may represent a potential therapeutic target for ALI treatment.